Kekhususan dalam Tahapan Penyerahan Perkara di Peradilan Militer - Ni Luh Ayu Widhiarcani Laksmidewi; Ni Nengah Adiyaryani (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Fields of law in Indonesia are a system that is interrelated and affects each other. That there are similarities and differences between each law, including in terms of its enforcement. For example, between the Criminal Procedure Law and the Procedural Law of Military Justice. These two areas of law have some similarities in terms of the stages of trials, but there are differences, one of which is the unfamiliarity of the pre-prosecution stage in the military courts. This study aims to find out the existence of the Commander in resolving cases and to find out the reasons for the unfamiliarity pre-prosecution stage in the Military Court. This research is a normative research with a statutory approach. In addition, this study also uses qualitative analysis techniques. English translation. The existence of the commander in the settlement of cases is part of his authority to punish. The commander in charge of the command unit and his subordinates actively participates in all stages of the examination in the military courts, both as a Superior who has the right to punish in the investigation and as a case-handling officer in the prosecution stage. The existence of the pre-prosecution stage in the Military Court will intersect with the principle of unity of command and the principle of the commander being accountable. These two principles are two important principles in addition to the principle of military interest in the Military Judiciary which is also the basis of the authority and existence of the commander in the military courts.